Validation of a short-range dispersion and deposition model using field-scale ammonia and methane release experiments - Christoph Häni; Albrecht Neftel; Christophe Flechard; Christof Ammann; Alex Valach; Thomas Kupper (Agricultural and Forest Meteorology, 2024)

Bi‐directional soil/atmosphere N 2 O exchange over two mown grassland systems with contrasting management practices - CHRISTOPHE R. FLECHARD; ALBRECHT NEFTEL; MARKUS JOCHER; CHRISTOF AMMANN; JÜRG FUHRER (Global Change Biology, 2005)
Nitrous oxide (N 2 O) fluxes from soil under mown grassland were monitored using static chambers over three growing seasons in intensively and extensively managed systems in Central Switzerland. Emissions were largest following the application of mineral (NH 4 NO 3 ) fertilizer, but there were also substantial emissions following cattle slurry application, after grass cuts and during the thawing of frozen soil. Continuous flux sampling, using automatic chambers, showed marked diurnal patterns in N 2 O fluxes during emission peaks, with highest values in the afternoon. Net uptake fluxes of N 2 O and subambient N 2 O concentrations in soil open pore space were frequently measured on both fields. Flux integration over 2.5 years yields a cumulated emission of +4.7 kgN 2 O‐N ha −1 for the intensively managed field, equivalent to an average emission factor of 1.1%, and a small net sink activity of −0.4 kg N 2 O‐N ha −1 for the unfertilized system. The data suggest the existence of a consumption mechanism for N 2 O in dry, areated soil conditions, which cannot be explained by conventional anaerobic denitrification. The effect of fertilization on greenhouse gas budgets of grassland at the ecosystem level is discussed.

Establishing the Link between Ammonia Emission Control and Measurements of Reduced Nitrogen Concentrations and Deposition - Mark A. Sutton; Willem A. H. Asman; Thomas Ellermann; J. A. Van Jaarsveld; Karin Acker; Viney Aneja; Jan Duyzer; Laszlo Horvath; Sergey Paramonov; Marta Mitosinkova; Y. Sim Tang; Beat Achermann; et al. (Environmental Monitoring and Assessment, 2003)

Process-based modelling of nitrous oxide emissions from different nitrogen sources in mown grassland - Martin Schmid; Albrecht Neftel; Marcel Riedo; Jürg Fuhrer (Nutrient Cycling in Agroecosystems, 2001)